Array-based comparative study of apomicitc and sexual Eragrostis curvula genotypes - Selva, Juan Pablo (2018)
Apomixis is an asexual reproductive process that results in seeds containing maternal clones since meiotic reduction and egg cell fertilization does not occur. Apomixis is common in polyploid grasses, and poorly represented in crop species of economic interest. A key goal in understanding the molecular basis of apomixis is the possible transference of this trait to species of agronomic relevance. Weeping lovegrass (Eragrostis curvula [Schrad.] Nees) is a perennial grass native to Southern Africa that reproduces by diplosporous apomixis. A custom 60-mer spots Agilent array was designed with 970 k probes based on a reference transcriptome constructed from inflorescence of sexual and apomictic genotypes. Eight independent hybridizations were performed with one-color Cy3 labelled samples (four apomictic and four sexual E. curvula genotypes). Data preprocessing and analysis was performed using the GeneSpring software v. 14.5. Platform quality was verified by Agilent spike-in controls. Normalization procedures consisted on percentile shift 75, background correction, median as baseline and reproductive mode as parameter. Individual probes from the array were considered to be differentially hybridized under the log2 transformed Fold Change data > 1 and p-values > 0.01 using unpaired t-test and multiple Benjamini-Hochberg correction. From these analyses 138 differential 60-mer sequences were obtained and four candidate genes strongly expressed in apomictic plants were identified. These genes could be have an important role in apomeiosis induction in weeping lovegrass and its relevance is currently being analysed through several complementary approaches, including in situ hybridization and obtention of Arabidopsis transformant.